Lima Metropolitana: ¿Una ciudad que se resiste a cambiar? - Aguilar, Cinthya (2021)
The purpose of this study is to analyze the way in which the perceptions of lifestyle and stereotypes that the inhabitants of the High Income areas of Metropolitan Lima have with respect to the residents of the inner peripheral districts have evolved. A qualitative design was applied by analyzing the results of a survey conducted on 151 people, who were divided into two groups by a filter: Residents of “inner peripheral districts” and those of “High Income Zones”. Likewise, a virtual survey was used as an instrument due to the current situation due to the Pandemic. The results obtained show that a negative thought and stereotype rooted in the com munity continues to be maintained and, furthermore, an increase in indifference and in the lack of interaction with these districts.